Ventral premotor cortex may be required for dynamic changes in the feeling of limb ownership: a lesion study. - Zeller, D; Gross, C; Bartsch, A; Johansen-Berg, H; Classen, J (2011)
The feeling of "body ownership" may be experimentally investigated by perceptual illusions. The "rubber hand illusion" (RHI) leads human subjects to experience an artificial hand as their own. According to functional imaging, the ventral premotor cortex (PMv) plays a key role in the integration of multisensory inputs allowing the "incorporation" of the rubber hand into body representation. However, causal structure-function relationships can only be obtained by lesion studies. Here, we tested the RHI in 70 stroke patients and in 40 age-matched healthy controls. Additionally, asomatognosia, the unawareness of one's own body parts, was assessed in a subgroup of 64 stroke patients. Ischemic lesions were delineated on diffusion-weighted magnetic resonance images and normalized. Right-hemispheric lesions were mirrored across the midline. Voxels that might be essential for RHI and/or somatognosia were defined by voxel-based lesion-symptom mapping. Probabilistic diffusion tractography was used to identify tracts passing through these voxels. Contralesional rubber hand illusion failure (RHIF) was observed in 18 (26%) of 70 stroke patients, an additional ipsilesional RHIF in seven of these patients. RHIF-associated lesion voxels were located subcortically adjacent to the insula, basal ganglia, and within the periventricular white matter. Tractography revealed fiber tract connections of these voxels with premotor, parietal, and prefrontal cortex. Contralesional asomatognosia was found in 18 (28%) of 64 stroke patients. In contrast to RHIF, asomatognosia-associated lesion voxels showed no connection with PMv. The results point to a role of PMv and its connections in mediating changes in the sense of limb ownership driven by multisensory stimulation.